(untitled) (Architecture Image Studies, 2025)
This study aims to analyze the effect of work efficiency on investigator performance mediated by investigator competence and moderated by organizational culture. This study was conducted using a survey method on 126 investigator personnel of the Special Criminal Investigation Directorate of the Southeast Sulawesi Regional Police. Data analysis was conducted using SEM with Smart PLS 4.0 software. The results of the data analysis obtained the results of work efficiency directly unable to improve investigator performance, but efficiency has a positive and significant effect on investigator competence and investigator competence has a positive and significant effect on investigator performance. Work efficiency has a positive and significant effect on investigator performance mediated by investigator competence, however work efficiency has a negative and insignificant effect moderated by organizational culture.